Cystic fibrosis transmembrane conductance regulator modulators attenuate platelet activation and aggregation in blood of healthy donors and COVID-19 patients. Issue 3 (23rd March 2023) - Asmus, Erik; Karle, Weronika; Brack, Markus C.; Wittig, Corey; Behrens, Felix; Reinshagen, Leander; Pfeiffer, Moritz; Schulz, Sabrina; Mandzimba-Maloko, Bertina; Erfinanda, Lasti; Perret, Paul L.; Michalick, Laura; et al.
Cystic fibrosis transmembrane conductance regulator (CFTR) modulators reduce agonist-induced platelet activation and function. CFTR modulators, such as ivacaftor, present a promising therapeutic strategy in thrombocytopathies, including severe COVID-19. https://bit.ly/3HJykdt Recent work identified the chloride channel cystic fibrosis transmembrane conductance regulator (CFTR), mutations of which can cause cystic fibrosis (CF), as an important regulator of platelet function, in that its loss or inhibition causes agonist-induced platelet hyperactivation [1]. Hence, activation of CFTR may conversely present a novel strategy to counteract platelet hypercoagulability. Of late, several groups of CFTR modulators have been clinically approved to boost the abundance and/or channel open probability of CFTR at the cell membrane in CF patients. While originally targeted for specific CFTR mutations, emerging evidence suggests that CFTR modulators may also increase channel activity of wild-type CFTR (CFTRwt ).